IMPLEMENTASI PERLINDUNGAN VARIETAS TANAMAN DALAM TRIPS AGREEMENT TERHADAP PRODUK PERTANIAN DI AMERIKA SERIKAT - dina rasyida (Fakultas Hukum Universitas Muhammadiyah Palu, 2021)
The weakness of international law in providing environmental protection, especially biodiversity, for the transfer of technology of transgenic plants emphasizes the importance of supervising the transfer process by technology receiving countries through various kinds of regulations. However, on the other hand, these regulations are often considered by developed countries as anti-competitive measures that can hinder the flow of technology transfer itself. The problems in this research are how to implement the protection of plant varieties in the TRIPs Agreement for agricultural products in the United States, and who is the holder of the right to protect plant varieties in the United States. The results showed that there were 3 types of plant variety protection against agricultural products in the United States, namely Plant Variety Protection, Plant Patents, and Utility Patents. The protection of plant variety in the United States has complied with the rules in the TRIPs Agreement. The holders of plant variety protection rights in the United States are individuals, public institutions, and corporations.